Strong and Dynamic CO2 Sorption in a Flexible Porous Framework Possessing Guest Chelating Claws - Liao, Pei-Qin; Zhou, Dong-Dong; Zhu, Ai-Xin; Jiang, Lu; Lin, Rui-Biao; Zhang, Jie-Peng; Chen, Xiao-Ming (Journal of the American Chemical Society, 2012)
Using a bis-triazolate ligand and tetrahedral Zn(II) ion, we synthesized a flexible porous coordination polymer functionalized with pairs of uncoordinated triazolate N-donors that can be used as guest chelating sites to give very high CO2 adsorption enthalpy and CO2/N2 selectivity. The dynamic CO2 sorption behavior could be monitored well by single-crystal X-ray diffraction.